Gender-specific social and environmental correlates of active travel to school in four European countries: the HBSC Study - Brindley, Catherina; Hamrik, Zdenek; Kleszczewska, Dorota; Dzielska, Anna; Mazur, Joanna; Haug, Ellen; Kopcakova, Jaroslava; Marques, Adilson; Altenburg, Teatske; Demetriou, Yolanda; Bucksch, Jens (Frontiers in Public Health, 2023)
Introduction: Despite health benefits, a large proportion of girls and boys in Europe do not travel to school actively. A better understanding of correlates associated with this behaviour could guide interventions. This study examines perceived social and environmental correlates of active travel to school (ACTS) from the 2017/18 Health Behaviour in School-aged Children survey (HBSC) in four European countries with a special emphasis on gender differences (n=22023).Logistic regression was conducted to analyze associations between perceived importance of each correlate and ACTS behaviour for 11-, 13-and 15-year old girls and boys from Germany, Czechia, Poland and Slovakia. All models were adjusted for age, family affluence and meeting WHO recommendations for moderate to vigorous physical activity.Results: Rates of ACTS significantly differed between girls and boys. In Czechia, 65% of girls and boys travelled to school actively, followed by Slovakia (61.4% girls and 58.4% boys), Poland (57.7% girls and 60.2% boys) and Germany (42.6% girls and 48.6% boys). Girls were less likely to actively travel to school compared to boys (OR: .92, 95%-CI: .87-.97). Increasing age (OR: .95, 95%-CI: .93-.97) and a greater distance to school index (OR: .89, 95%-CI: .88-.90) were both negatively associated with ACTS. The perceived importance of living closer to school and of road and neighborhood safety was positively associated with ACTS, with a stronger association in boys than in girls for neighborhood safety. On the contrary, the perceived importance of having people to walk with was negatively associated with ACTS, with a stronger association in girls (OR: .74, 95%-CI: .65-.84) than in boys (OR:.77, 95%-CI: .66-.88).Discussion: This study provides insights into perceived social and environmental correlates associated with ACTS behaviour. Future research should take gender-specific perceptions and include more in-depth investigations of correlates encouraging ACTS, especially considering social aspects, safety issues, and the structuring of the environment in different cultural settings.